A anterioridade da responsabilidade em Emmanuel Levinas - Longo, Giovan (2019)
The presented dissertation intends to explore the theme of responsibility in Emmanuel Levinas' work, more specifically about of responsibility as prior to individual freedom and to the individual himself as an awareness of himself and of the world. Such responsibility will be understood as central to the emergence of the subject of self-identity capable of consciously perceiving himself and the world. To do so, in the first chapter will be presented the conceptions of freedom and responsibility to whom we refer when using the Levinasian criticism on Western thought. Such criticism will also be explored in this first chapter. In the second chapter we will look at the conception of the human in Levinas's thinking by showing how the unconditional responsibility for the other is contained in the self's identity. In the third chapter we will present what Levinas understands by responsibility and how it makes the self a subject committed to the other and to the world. In the fourth and last chapter, the need to review the concept of freedom, since responsibility for the other requires that the self does not take place itself first, such a concept will be presented as Levinas re-signifies it. In the face of all this, the work that will be presented intends to be an exposition of how the self would have to act before the other and the world. Such a need, as we will see, is contained in the very formation of the selfconscious self and the world. To deny it would be to deny what the human is.